2002
DOI: 10.1002/ijc.10903
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the human Ly‐6 antigens, the newly annotated member Ly‐6K included, as molecular markers for head‐and‐neck squamous cell carcinoma

Abstract: The E48 antigen is a successfully explored molecular marker for the diagnosis and therapy of HNSCC. The applicability of E48 as an HNSCC-associated antigen, however, is restricted due to its heterogeneous expression in 30% of tumors; and identification of additional target antigens is therefore desired. E48 belongs to the Ly-6 antigen family, comprising a group of highly homologous, low m.w., GPIanchored surface proteins, of which some show tissue-restricted expression patterns. To identify novel human HNSCC-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 46 publications
1
68
0
Order By: Relevance
“…LY6K has been reported as a testicular cancer antigen that is not only a target antigen for head-and-neck squamous cell carcinoma but also a diagnostic marker for breast cancer and a serologic biomarker and therapeutic target for lung and esophageal carcinomas (7)(8)(9). Activating LY6K results in an increase in cell invasive motility and metastasis, whereas a low level of LY6K reduces cell mobility in breast cancer cells (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LY6K has been reported as a testicular cancer antigen that is not only a target antigen for head-and-neck squamous cell carcinoma but also a diagnostic marker for breast cancer and a serologic biomarker and therapeutic target for lung and esophageal carcinomas (7)(8)(9). Activating LY6K results in an increase in cell invasive motility and metastasis, whereas a low level of LY6K reduces cell mobility in breast cancer cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…The LY6K was first identified as a molecular marker for head-and-neck squamous cell carcinoma (7). Previous studies have shown that cancer-testis antigen LY6K could be a diagnostic biomarker and a therapeutic target for breast cancer, nonsmall cell lung carcinoma, bladder cancer, and esophageal squamous cell carcinoma (8 -11).…”
mentioning
confidence: 99%
“…HNSCC cell lines (except JCRB 1027 SAT) were kindly provided by Dr. R. H. Brakenhoff (Department of Otolaryngology/Head-Neck Surgery, VUMC Amsterdam, the Netherlands). [19][20][21] The HNSCC cell line JCRB 1027 SAT was obtained from the Japan Health Science Foundation, Health Science Research Resources Bank. Cells were grown as monolayers (except DU4475 cells) in DMEM medium (Invitrogen, Karlsruhe, Germany) supplemented with 10% fetal calf serum (PAA Labora-tories GmbH, Pasching, Austria) and 2 mM L-glutamine (Invitrogen) at 37°C in a humidified 10% CO 2 atmosphere.…”
Section: Cell Culturementioning
confidence: 99%
“…LY6K overexpression has been confirmed in several malignancies including head and neck squamous cell carcinomas as well as breast, lung, bladder, and esophageal cancers [12,13,[15][16][17][18][19]. LY6K overexpression is associated with a poorer prognosis in patients with non-small cell lung carcinomas as well as those with esophageal squamous cell carcinomas [12].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the status of LY6K protein in clinical gastric cancer samples embedded in paraffin blocks, we performed immunohistochemistry as described previously [12,15,16]. Briefly, rabbit polyclonal antihuman LY6K antibodies (TM38) were applied to the sections after blocking endogenous peroxidases and proteins.…”
Section: Analysis Of Ly6k Expression In Gastric Cancermentioning
confidence: 99%